Modeling and Real-World Validation of Home Energy Management Systems: Photovoltaic Generation, Battery Energy Storage, and Bidirectional Grid Connection - Janthong, Supakan; Boonrat, Kanitsorn; Rojchaya, Sittisak (Journal of Renewable Energy and Smart Grid Technology, 2026)
This article presents comprehensive modeling, simulation, and real-world validation of a Home Energy Management System (HEMS) using MATLAB/Simulink. The model integrates photovoltaic (PV) panels with single-diode equivalent circuits, lithium-ion battery energy storage systems (BESS) with electrochemical modeling, unidirectional boost converters for PV voltage regulation, bidirectional DC/DC converters for battery control, bidirectional DC/AC inverters with sinusoidal PWM for grid synchronization, and utility grid connection to enhance energy efficiency and reduce grid dependency. Five operational scenarios were designed and tested: (1) normal operation with PV as primary source, (2) high load exceeding PV capacity, (3) low solar irradiance requiring battery support, (4) battery charging during PV surplus, and (5) grid export of excess energy. Each scenario was analyzed under varying environmental conditions (solar irradiance 0–650 W/m²) and load profiles. Simulation results demonstrate effective energy balancing through priority-based control (PV → Battery → Grid), with response times under 200 ms, DC bus voltage stability within ±2%, and AC power quality meeting grid standards (THD < 3%, power factor > 0.98). Real-world validation used 30 days of operational data from a 5 kW PV system with 10 kWh battery storage monitored through the FusionSolar platform. Experimental results showed strong model accuracy with an average MAPE of 4.2%. Performance metrics demonstrated 65.2% PV self-consumption under normal conditions, 37% peak demand reduction during high-load scenarios, 92.4% battery charging efficiency, and 96.1% grid export inverter efficiency. The validated model confirms the HEMS performance evaluation and demonstrates the practical feasibility and economic viability of integrated PV-battery-grid systems.